Generalized Performance Measures of X- Control Charts Based on Different Sampling Schemes. (4th June 2019) - Mehmood, Rashid; Lee, Muhammed Hisyam; Riaz, Muhammad; Ali, Iftikhar
Abstract : Different versions ofX - control chart structure are available under various ranked set strategies. In these control charts, computation of performance measures was carried out through Monte Carlo simulation method (MCSM). In this article, we have defined a generalized structure ofX - control charts under variant sampling strategies followed by derivation of their different performance measures. For the derivation of different performance measures, we have proposed pivotal quantity. For comparative analysis, we have presented results of generalized performance measures by involving numerical method (NM) as computation. We found that values of generalized performance measures based on NM are almost similar to values of performance measures based on MCSM. Also, NM is time efficient and can be considered as an alternative of MCSM.